2009
DOI: 10.1007/s10295-009-0568-1
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of esterase and lipase from Haloarcula marismortui

Abstract: The present study was conducted to investigate the capability of Haloarcula marismortui to synthesize esterases and lipases, and the effect of physicochemical conditions on the growth and the production of esterases and lipases. Finally, the effect of NaCl concentration and temperature on esterase and lipase activities was studied using intracellular crude extracts. In order to confirm the genomic prediction about the esterase and lipase synthesis, H. marismortui was cultured on a rich medium and the crude ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 28 publications
2
40
0
3
Order By: Relevance
“…For instance, Haloarcula marismortui, a halophilic archaeon whose genome was sequenced contains genes encoding for putative esterase and lipase. These genomic predictions have been verified recently (Camacho et al 2009). They reported that Haloarcula marismortui displays esterase and lipase activity intracellularly and extracellularly.…”
Section: Biotechnological Importance Of Archaeamentioning
confidence: 61%
See 1 more Smart Citation
“…For instance, Haloarcula marismortui, a halophilic archaeon whose genome was sequenced contains genes encoding for putative esterase and lipase. These genomic predictions have been verified recently (Camacho et al 2009). They reported that Haloarcula marismortui displays esterase and lipase activity intracellularly and extracellularly.…”
Section: Biotechnological Importance Of Archaeamentioning
confidence: 61%
“…They reported that Haloarcula marismortui displays esterase and lipase activity intracellularly and extracellularly. While lipase was accumulated mainly extracellular, esterase was generally accommodated intracellular (Camacho et al, 2009). The esterase and lipase genes of Pyrococcus furiosus, a hyperthermophilic archaeon, have been cloned in E. coli and functional properties have been determined.…”
Section: Biotechnological Importance Of Archaeamentioning
confidence: 99%
“…4C). Results indicated that Haloarcula hispanica 2TK2 lipase was stable in a wide range of salt concentrations unlike most of the halophilic lipases 31, 32 . The lipase preserved its activity even at low salt concentrations.…”
Section: Effect Of Temperature Ph and Nacl Concentration On Enzyme Amentioning
confidence: 97%
“…Many microorganisms are found in fermented fish products that can produce extracellular lipases that catalyze the hydrolysis of triacylglycerols to glycerol and free fatty acids, including low molecular weight volatile fatty acids, such as acetic acid, propionic acid and butyric acid (Fukami et al 2002). These later components are associated with the aroma and flavor in fermented fish products (Camacho et al 2009). The aim of this research was to isolate, identify and screen the lipase activity of halophilic bacterial strains from Thai fermented fish products.…”
Section: Introductionmentioning
confidence: 99%
“…(Gupta et al 2004), Geobacillus sp. TW1 (Li & Zhang 2005), Haloarcula marismortui (Camacho et al 2009), Bacillus sp. strain DVL2 (Kumar et al 2012), B. mesenterichs, B. subtilis, B. cereus (Miettinen et al 2013) and Idiomarina sp.…”
mentioning
confidence: 99%